Impact of urban block configuration and direction on urban temperature increase in hot, humid regions / Lin Yola and Ho Chin Siong - Yola, Lin; Ho, Chin Siong (2015)
Urban temperature increase contributes significant effect to global warming. This phenomenon has been addressed as the real impact of rapid development which occurs in the urban area, which causes urban heat islands (UHIs). One of the influencing factors is building typology that forms urban block configuration. This study which was conducted in Kuala Lumpur, Malaysia aims to investigate the impact of varies of urban block configurations on the air temperature and the variables that affect it. The hypothetical model simulation was used to analyse the measures. It finds out that urban block creates the shades to the outdoor environment which blocks the surface from direct solar radiation. However, it also depends on the direction of urban block configuration towards the expose angle of solar radiation. As the conclusion, the right scenario of urban block configuration and the choice of its direction mitigate the urban temperature increase. This finding suggests planners and designers to perform the similar quantitative analysis in the earlier stage of planning.